Nanocellulose-collagen-apatite composite associated with osteogenic growth peptide bone regeneration - Saska, Sybele [UNESP]; Teixeira, Lucas Novaes; de Castro Raucci, Larissa Moreira Spinola; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Franchi, Leonardo Pereira; dos Santos, Raquel Alves; Santagneli, Silvia Helena [UNESP]; Capela, Marisa Veiga [UNESP]; de Oliveira, Paulo Tambasco; Takahashi, Catarina Satie; Gaspar, Ana Maria Minarelli [UNESP]; Messaddeq, Younès [UNESP]; et al. (Elsevier, 2017)
Despite advances in the field of biomaterials for bone repair/regeneration, some challenges for developing an ideal bone substitute need to be overcome. Herein, this study synthesized and evaluated in vitro a nanocomposite based on bacterial cellulose (BC), collagen (COL), apatite (Ap) and osteogenic growth peptide (OGP) or its C-terminal pentapeptide [OGP(10-14)] for bone regeneration purposes. The BC-COL nanocomposites were successfully obtained by carbodiimide-mediated coupling as demonstrated by spectroscopy analysis. SEM, FTIR and 31P NMR analyses revealed that in situ synthesis to apatite was an effective route for obtaining of bone-like apatite. The OGP-containing (BC-COL)-Ap stimulated the early development of the osteoblastic phenotype. Additionally, the association among collagen, apatite, and OGP peptides enhanced cell growth compared with OGP-containing BC-Ap. Furthermore, none of the nanocomposites showed cytotoxic, genotoxic or mutagenic effects. These promising results suggest that the (BC-COL)-Ap associated with OGP peptides might be considered a potential candidate for bone tissue engineering applications.
Keywords: Bacterial cellulose; Biopolymer; Bone regeneration; Composite; Peptide; Tissue engineering